Androgendeprivationstherapie und kardiovaskuläre Morbidität beim Prostatakarzinom: ein narratives Review - Klemm, Jakob; von Deimling, Markus; Fisch, Margit; Kramer, Gero; Tilki, Derya; Steuber, Thomas; von Amsberg, Gunhild; Hengstenberg, Christian; Shariat, Shahrokh F (Urologie (Heidelberg, Germany), 2024)
Prostate cancer is the most common malignancy in men, mostly affecting older men who harbor an increased prevalence of cardiovascular disease and metabolic syndrome. Androgen deprivation therapy (ADT), the standard therapy for various stages of prostate cancer, further increases the risk for cardiovascular disease and for metabolic syndrome. Therefore, screening for cardiovascular risk factors should be performed prior to the initiation of ADT, and, if necessary, cardiological evaluation and interdisciplinary management should be provided during and after completion of ADT. Moreover, the use of a gonadotropin-releasing hormone (GnRH) antagonist may help reduce cardiovascular risk in patients with cardiovascular disease.
Keywords: Male; Gonadotropin-releasing hormone-Agonist; Prostatic Neoplasms; Aged; Cardiovascular morbidity; mužské pohlaví; senioři; metabolický syndrom; Gonadotropin-releasing hormone-Antagonist; Androgens; antagonisté androgenů; Androgen Antagonists; Metabolic Syndrome; Androgen deprivation therapy; kardiovaskulární nemoci; lidé; androgeny; Humans; nádory prostaty; Prostate neoplasms; Gonadotropin-Releasing Hormone; hormon uvolňující gonadotropiny; Cardiovascular Diseases